Speaking of Teaching$1! =s Inclinations, Inspirations, and Innerworkings - Cohen, Avraham; Porath, Marion; Clarke, Anthony; Bai, Heesoon; Leggo, Carl.; Meyer, Karen; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Teaching is a richly multifaceted endeavor. It isn$1 (Bt always easy to know just where we should focus our thinking and our dialogue. In Speaking of Teaching, six educators talk about their inner selves. They bring the inside out for their own self-exploration. And they bring the inside out for us to view and learn from. They also question the boundaries between the inner and the outer and whether existence can be dichotomized in this way. Gary Poole, Professor, Faculty of Medicine, The University of British Columbia, 3M Teaching Fellow. The authors of this collection explore the many ways to remain present in the midst of the trifling but perpetual swirl of events, thoughts, distractions, and how they, as they are at, what T. S. Eliot called, the still point of the turning world, find profound meaning in their work as educators. A deeply moving collection that allowed me too, while reading it, to rediscover that still point without which there would be no dance, and there is only the dance. Gerda Wever, PhD, editor and publisher, The Write Room Presss
Keywords: Education; Education; Education (general).